2022
DOI: 10.1177/10711007221114123
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Chevron-Akin for Correction of Moderate and Severe Hallux Valgus Deformities: Clinical and Radiologic Outcomes With a Minimum 2-Year Follow-up

Abstract: Background: The minimally invasive chevron-Akin (MICA) technique has already demonstrated efficacy compared with other known surgical treatments for mild to moderate hallux valgus (HV). MICA combines percutaneous osteotomies with the benefits of modern, rigid internal fixation. The aim of study was to evaluate the radiographic parameters, clinical improvement, and potential complications in moderate to severe HV cases, operated using the MICA technique. Methods: Retrospective study including 70 feet with HV op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
17
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 69 publications
8
17
0
Order By: Relevance
“…In recent clinical studies and systemic review of third generation minimally invasive surgery for hallux valgus, overall complication rates of 8.4% to 24.2% have been reported. 6,23,25,29 Our overall complication rate was 20.7% and reoperation rate was 8.6%, which is similar to other reports. 16 Two most common major complications were screw irritation and recurrence.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In recent clinical studies and systemic review of third generation minimally invasive surgery for hallux valgus, overall complication rates of 8.4% to 24.2% have been reported. 6,23,25,29 Our overall complication rate was 20.7% and reoperation rate was 8.6%, which is similar to other reports. 16 Two most common major complications were screw irritation and recurrence.…”
Section: Discussionsupporting
confidence: 90%
“…Lewis et al 26 reported significant improvement in both mean HVA (44.1-11.5 degrees) and mean 1-2 IMA (17.5-5.1 degrees) in cases with severe HV after MICA. Carvalho et al 6 reported significant reductions in radiographic parameters, including the HVA, 1-2 IMA, and DMAA, in cases with moderate to severe HV.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…5,21,24,28,29,31-33,35,42,45,50 Studies have suggested the radiographic deformity correction that can be achieved using certain MIS techniques in severe deformities is potentially greater than reported in a range of open techniques with similar complication rates. 7,12,31,35…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, there is a learning curve associated with MIS hallux valgus surgery that has been shown to be between 60 and 70 cases, with improved results after this, which could affect outcomes of MIS hallux valgus correction. 4 , 5 , 9 , 16 We believe the result of nonunion in MIS hallux valgus correction may be multifactorial and include various levels of skill, surgical technique used, and fixation techniques. However, it is beyond the scope of this review to identify the causality of the nonunions and determine if these factors played a role.…”
Section: Discussionmentioning
confidence: 99%